Battery packaging material, battery, method for manufacturing battery packaging material and battery, and polyester film

The laminate structure of a battery packaging material with a surface-oriented polyester film layer addresses adhesion and printability issues, ensuring high-quality image formation while maintaining thinness and lightweight characteristics.

KR103040971B1Active Publication Date: 2026-10-30DAI NIPPON PRINTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020257021392
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-12-06
Filing Date
2018-12-06
Publication Date
2026-10-30
Estimated Expiration
2038-12-06

AI Technical Summary

Technical Problem

Conventional battery packaging materials face challenges in achieving thinness and lightweight designs due to limitations in shape diversity and adhesion issues when printing directly on polyester film surfaces, leading to ink expansion and distortion, which complicates the formation of desired images.

Method used

A battery packaging material with a laminate structure comprising a substrate layer, a barrier layer, and a heat-fusible resin layer, where the substrate layer is composed of a polyester film, and the surface orientation of the polyester film layer is optimized to ensure a specific ratio of infrared absorption peak intensities, enhancing printability and adhesion.

Benefits of technology

The optimized laminate structure allows for improved printability and adhesion, enabling high-quality image formation on the battery packaging material without increasing thickness or weight, thus supporting the trend towards thinner and lighter battery designs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112025071867213-PAT00006_ABST
    Figure 112025071867213-PAT00006_ABST
Patent Text Reader

Abstract

A battery packaging material comprising, at least, a laminate having a substrate layer, a barrier layer, and a heat-fusible resin layer located at the outermost surface in this order, wherein the outermost surface of the substrate layer is composed of a polyester film layer, and when infrared absorption spectra are acquired in 18 directions in 10° increments from 0° to 170° with respect to the surface of the polyester film layer using the total reflection method of Fourier transform infrared spectroscopy, satisfying the following equation: Ymax / Ymin<1.4
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a packaging material for batteries, a battery, a method for manufacturing the same, and a polyester film. Background Technology

[0002] Conventionally, although various types of batteries have been developed, packaging materials have become an indispensable component for encapsulating battery elements such as electrodes and electrolytes in all of them. Conventionally, metal packaging materials have been widely used as packaging for batteries.

[0003] Meanwhile, with the recent increase in performance of electric vehicles, hybrid electric vehicles, computers, cameras, and mobile phones, batteries are required to have various shapes, as well as be thinner and lighter. However, conventional metal packaging materials for batteries have the drawback that it is difficult to keep up with the diversification of shapes, and furthermore, there are limitations to weight reduction.

[0004] Therefore, recently, a film-type laminate in which a substrate, a barrier layer, and a heat-fusible resin layer are sequentially laminated has been proposed as a battery packaging material that is easy to process into various shapes and can achieve thinning or lightweighting (see, for example, Patent Document 1). In such a battery packaging material, a concave portion is generally formed by cold forming, a battery element such as an electrode or an electrolyte is placed in the space formed by this concave portion, and the heat-fusible resin layers are heat-fused together, thereby obtaining a battery in which the battery element is housed inside the battery packaging material.

[0005] In various packaging materials composed of the above-mentioned laminate, a method of imprinting on the packaging material (generally referred to as reverse printing) is widely adopted by printing ink on the surface of a substrate layer to form a barcode, pattern, character, etc., and laminating an adhesive or barrier layer on the substrate layer on the printed side. However, if such a printed surface exists between the substrate layer and the barrier layer, the adhesion between the substrate layer and the barrier layer is reduced, making it easy for delamination to occur between the layers. In particular, since high safety is required for batteries to which packaging materials for batteries are applied, the method of imprinting by such reverse printing is avoided in battery packaging materials. Therefore, conventionally, when forming an imprint such as a barcode on a battery packaging material, a method of attaching a seal with the imprint formed thereon to the surface of the substrate layer is generally adopted. Prior art literature

[0006] Japanese Patent Publication No. 2008-287971 The problem to be solved

[0007] However, when a sealing material with a formed factor is attached to the surface of a substrate layer, the thickness or weight of the battery packaging material increases. Accordingly, considering the recent trend toward further thinning and lightweighting of battery packaging materials, the inventors investigated a method of forming the seal directly on the surface of a substrate layer of a battery packaging material by printing ink.

[0008] Methods for printing directly onto the surface of a substrate layer of a battery packaging material by printing ink include, for example, pad printing (also called tampo printing) and inkjet printing. Pad printing is a printing method as follows: First, ink is applied to the concave areas of a flat plate on which the pattern to be printed is etched. Next, a silicone pad is placed over the concave areas and pressed to transfer the ink to the silicone pad. Then, the ink transferred to the surface of the silicone pad is transferred to the printing target to form an image on the printing target. Since such pad printing utilizes an elastic silicone pad or the like to transfer the ink to the printing target, it is easy to print on the surface of the battery packaging material after molding, and it has the advantage of being able to print on the battery after the battery element has been encapsulated in the battery packaging material. In addition, inkjet printing has the same advantages.

[0009] However, the inventors have investigated and found a problem in which, in a packaging material for batteries having a polyester film layer on the outermost surface, when ink is printed on the surface of the polyester film layer, the expansion of the ink on the surface of the polyester film layer becomes improper, or the dots of the printed portion formed by the ink tend to become distorted, making it difficult to form an image of the desired size and shape.

[0010] Under such circumstances, the main objective of the present invention is to provide a battery packaging material having a polyester film layer on its outermost surface, wherein the surface of the polyester film layer has excellent material properties. means of solving the problem

[0011] The inventors have conducted a thorough investigation to solve the above problems. As a result, it was discovered that a battery packaging material satisfying the following equation, which is composed of a laminate having, at least, a substrate layer located on the outermost surface, a barrier layer, and a heat-fusible resin layer in that order, wherein the outermost surface of the substrate layer is composed of a polyester film layer, and when infrared absorption spectra are acquired in 18 directions at 10° increments from 0° to 170° on the surface of the polyester film layer using the total reflection method of Fourier transform infrared spectroscopy, the expansion of ink on the surface of the polyester film layer becomes improper or the dots of the printed portion become distorted, and excellent printing performance is exhibited.

[0012] Y max / Y min <1.4

[0013] Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by.

[0014] Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by.

[0015] Maximum value Y max and minimum value Y min In calculating, for each of the above 18 directions, Y 1340 / Y 1410 Calculate , and among them, the maximum value Y for each max and minimum value Y min Select .

[0016] The present invention was completed by further examining these findings.

[0017] That is, the present invention provides an invention of the form presented below.

[0018] Claim 1. At least, the laminate comprises a substrate layer located on the outermost surface, a barrier layer, and a heat-fusible resin layer in this order, and

[0019] The outermost surface of the above substrate layer is composed of a polyester film layer, and

[0020] A battery packaging material that satisfies the following equation when infrared absorption spectra in 18 directions from 0° to 170° in 10° increments are acquired for the surface of the polyester film layer using the total reflection method of Fourier transform infrared spectroscopy.

[0021] Y max / Y min <1.4

[0022] Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by.

[0023] Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by.

[0024] Claim 2. A battery packaging material described in Claim 1, used for the purpose of performing printing on the surface of the polyester film layer.

[0026] Claim 3. A packaging material for batteries described in Claim 1 or 2, in accordance with the method specified in JIS B 0601-2001, wherein the arithmetic mean roughness Ra measured on the surface of the polyester film layer is 10 nm or more.

[0027] Claim 4. Between the barrier layer and the heat-fusible resin layer, an adhesive layer is provided, and

[0028] A packaging material for a battery as described in any one of claims 1 to 3, wherein the adhesive layer comprises an acid-modified polyolefin.

[0029] Clause 5. The acid-modified polyolefin of the adhesive layer is maleic anhydride-modified polypropylene, and

[0030] A packaging material for batteries described in claim 4, wherein the heat-fusible resin layer comprises polypropylene.

[0031] Claim 6. A packaging material for a battery described in any one of claims 4 to 5, wherein the adhesive layer is a cured product of a resin composition comprising at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group.

[0032] Claim 7. A packaging material for a battery described in any one of claims 4 to 6, wherein the adhesive layer is a cured product of a resin composition comprising at least one curing agent selected from the group consisting of oxygen atoms, heterocyclic rings, C=N bonds, and COC bonds.

[0033] Claim 8. A packaging material for a battery as described in any one of Claims 4 to 7, wherein the adhesive layer comprises at least one selected from the group consisting of urethane resin, ester resin, and epoxy resin.

[0034] Claim 9. A packaging material for a battery as described in any one of Claims 4 to 8, wherein the thickness of the adhesive layer is 50 μm or less.

[0035] Claim 10. A packaging material for a battery as described in any one of Claims 4 to 8, wherein the thickness of the adhesive layer is 10㎛ or more and 50㎛ or less.

[0036] Claim 11. A packaging material for a battery described in any one of Claims 4 to 10, which is a co-extruded laminate of the adhesive layer and the heat-fusible resin layer.

[0037] Claim 12. A packaging material for a battery as described in any one of Claims 1 to 11, wherein the thickness of the polyester film layer is 10㎛ or more and 50㎛ or less.

[0038] Claim 13. A packaging material for a battery as described in any one of Claims 1 to 12, wherein the polyester film layer is composed of an extended polyester film.

[0039] Claim 14. A battery packaging material described in any one of Claims 1 to 13, satisfying the following equation when infrared absorption spectra in 18 directions from 0° to 170° in 10° increments are acquired on the surface of the polyester film layer using the total reflection method of Fourier transform infrared spectroscopy.

[0040] 1.1≤Y max / Y min <1.4

[0041] Claim 15. At least one surface of the barrier layer is provided with an acid-resistant film, and

[0042] With respect to the above acid-resistant film, when analyzed using time-of-flight secondary ion mass spectrometry, Ce2PO4 + , CePO4 - , CrPO2 + , and CrPO4 - A battery packaging material described in any one of claims 1 to 14, wherein a peak originating from at least one selected from the group consisting of

[0043] Claim 16. A battery packaging material described in any one of Claims 1 to 15, comprising an acid-resistant coating on at least one surface of the barrier layer, the coating comprising at least one selected from the group consisting of a phosphorus compound, a chromium compound, a fluoride, and a triazinethiol compound.

[0044] Claim 17. A battery packaging material described in any one of claims 1 to 16, having an acid-resistant film containing a cerium compound on at least one surface of the barrier layer.

[0045] Claim 18. A packaging material for a battery described in any one of Claims 1 to 17, wherein a lubricant is present on at least one of the interior and surface of the polyester film layer.

[0046] Claim 19. A battery having at least a positive electrode, a negative electrode, and an electrolyte, wherein the battery element is contained within a packaging body formed by a battery packaging material described in any one of claims 1 to 18.

[0047] Claim 20. A battery described in Claim 19 having a factoring portion on the surface of the polyester film layer.

[0048] Claim 21. A receiving process for receiving a battery element having at least a positive electrode, a negative electrode, and an electrolyte within a packaging body made of a battery packaging material described in any one of Claims 1 to 18, and

[0049] A process of performing printing on the surface of the polyester film layer at least before and after the above acceptance process.

[0050] A method for manufacturing a battery, comprising

[0051] Paragraph 22. A polyester film for use in a polyester film layer located on the outermost surface of a packaging material for batteries, wherein

[0052] A polyester film that satisfies the following equation when infrared absorption spectra in 18 directions from 0° to 170° in 10° increments are acquired for the surface of the polyester film using the total reflection method of Fourier transform infrared spectroscopy.

[0053] Y max / Y min <1.4

[0054] Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by.

[0055] Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by.

[0056] Clause 23. Use as a polyester film layer located on the outermost surface of a battery packaging material, wherein, when infrared absorption spectra are acquired in 18 directions at 10° intervals from 0° to 170° for the surface of a polyester film using the total reflection method of Fourier transform infrared spectroscopy, the polyester film satisfies the following equation.

[0057] Y max / Y min <1.4

[0058] Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410It is the maximum value among the values ​​divided by.

[0059] Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by. Effects of the invention

[0060] According to the present invention, a battery packaging material having a polyester film layer on its outermost surface can be provided, wherein the surface of the polyester film layer has excellent material properties. Brief explanation of the drawing

[0061] [Fig. 1] This is a drawing showing an example of the cross-sectional structure of a battery packaging material according to the present invention. [Fig. 2] This is a drawing showing an example of the cross-sectional structure of the battery packaging material of the present invention. [Fig. 3] This is a drawing showing an example of the cross-sectional structure of the battery packaging material of the present invention. [Fig. 4] This is an image of the printed portion formed on the surface of a biaxially stretched polyethylene terephthalate film, observed with a laser microscope for Example 2. [Fig. 5] This is an image of the formed portion on the surface of a biaxially stretched polyethylene terephthalate film, observed with a laser microscope for Comparative Example 7. Specific details for implementing the invention

[0062] The battery packaging material of the present invention is composed of a laminate having, at least, a substrate layer located at the outermost surface, a barrier layer, and a heat-sealable resin layer in that order, wherein the outermost surface of the substrate layer is composed of a polyester film layer, and is characterized by satisfying the following equation when infrared absorption spectra are acquired in 18 directions of 10° increments from 0° to 170° with respect to the surface of the polyester film layer using the total reflection method of Fourier transform infrared spectroscopy. The battery packaging material of the present invention will be described in detail below.

[0063] Y max / Y min <1.4

[0064] In the above equation, Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 (CH2 vertical vibration), wavenumber 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by (C=C stretching vibration).

[0065] Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by.

[0066] Maximum value Y max and minimum value Y min In calculating, for each of the above 18 directions, Y 1340 / Y 1410 Calculate , and among them, the maximum value Y for each max and minimum value Y min Select .

[0067] The packaging material for batteries according to the present invention is described in detail below. Furthermore, regarding numerical ranges in this specification, a numerical range indicated by "~" means "greater than or equal to" or "less than or equal to." For example, the notation 2 to 15 mm means 2 mm or more and 15 mm or less.

[0068] 1. Laminated structure of battery packaging materials

[0069] The battery packaging material of the present invention is a laminate having a substrate layer (1) located on the outermost surface, a barrier layer (3), and a heat-fusible resin layer (4) in this order, for example as shown in FIG. 1. In addition, the outermost surface of the substrate layer (1) is composed of a polyester film layer. In the battery packaging material of the present invention, the polyester film layer is on the outermost layer side, and the heat-fusible resin layer (4) is on the innermost layer. That is, when assembling the battery, the heat-fusible resin layers (4) located on the surrounding edges of the battery element heat-fusify with each other to seal the battery element, thereby encapsulating the battery element.

[0070] As described below, the substrate layer (1) may have another layer in addition to the polyester film layer. Furthermore, if the substrate layer (1) has the other layer, the polyester film layer and the other layer may be bonded by an adhesive layer. In addition, the battery packaging material of the present invention may have an adhesive layer (2) between the substrate layer (1) and the barrier layer (3) as needed to improve their adhesion, for example, as shown in FIG. 2. In addition, an adhesive layer (5) may be formed between the barrier layer (3) and the heat-sealable resin layer (4) as needed to improve their adhesion.

[0071] The total thickness of the laminate constituting the battery packaging material of the present invention is not particularly limited, but in terms of making the total thickness of the laminate as thin as possible while improving moldability, preferably about 180 μm or less, more preferably about 35 to 160 μm, and even more preferably about 45 to 150 μm.

[0072] The battery packaging material of the present invention can preferably be used for applications where printing is performed on the surface of a polyester film layer located on the outermost surface. Suitable printing methods using ink include, for example, the aforementioned pad printing and inkjet printing, and particularly, inkjet printing. Suitable solvents included in the ink include, preferably, methyl ethyl ketone, acetone, isopropyl alcohol, ethanol, etc. The solvent may be used as a single type or in combination of two or more types.

[0073] 2. Each layer forming the packaging material for batteries

[0074] [Recording layer (1)]

[0075] In the battery packaging material of the present invention, the substrate layer (1) is a layer located on the outermost surface. The outermost surface of the substrate layer (1) is composed of a polyester film layer. Furthermore, in the present invention, even when a lubricant is present on the surface of the polyester film layer, the polyester film layer to which the lubricant is attached constitutes the outermost surface of the battery packaging material. Therefore, even with respect to the substrate layer (1) on which a lubricant is present on the surface, the substrate layer (1) is a layer located on the outermost surface of the battery packaging material.

[0076] In the packaging material for a battery according to the present invention, the polyester film layer constituting the outermost surface is characterized by satisfying the following equation when infrared absorption spectra in 18 directions from 0° to 170° in 10° increments are acquired for the surface of the polyester film layer using the total reflection method of Fourier transform infrared spectroscopy.

[0077] Y max / Y min <1.4

[0078] Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by.

[0079] Also, Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by.

[0080] Maximum value Y max and minimum value Y min In calculating, for each of the above 18 directions, Y 1340 / Y 1410 Calculate , and among them, the maximum value Y for each max and minimum value Y min Select .

[0081] In the battery packaging material of the present invention, the outermost surface of the substrate layer is composed of a polyester film layer, and furthermore, since the polyester film layer possesses the aforementioned specific surface orientation, excellent printability is exhibited despite the outermost surface being composed of a polyester film. As for this mechanism, for example, it can be conceived as follows. That is, in the battery packaging material of the present invention, since the polyester film layer constituting the outermost surface possesses the aforementioned specific surface orientation, the orientation degree of the polyester molecules within the polyester film layer can be said to be low. For this reason, it is believed that ink spreads easily in a uniform direction on the surface of the polyester film layer, and excellent printability is exhibited. In conventional packaging materials for batteries, when a polyester film layer is used as the substrate layer, a polyester film with a high degree of orientation of polyester molecules was used by greatly stretching the polyester film to improve moldability. However, in the present invention, excellent typing performance is exhibited by having the above-mentioned surface orientation with respect to the polyester film layer constituting the outermost surface. There are methods to improve typing performance by presenting a lubricant on the surface of the substrate layer or by performing a surface treatment on the substrate layer, and this method may be adopted in the present invention. However, in the present invention, excellent typing performance is exhibited even though the outermost surface is composed of a polyester film, because the polyester film layer possesses the above-mentioned specific surface orientation.

[0082] The specific measurement conditions for the infrared absorption spectrum are as follows. Additionally, the measurement of the infrared absorption spectrum at the surface of the polyester film layer can be performed while laminated to the battery packaging material.

[0083] (Measurement conditions of infrared absorption spectrum)

[0084] Spectrometer (with single-reflection ATR attachment)

[0085] Detector: MCT(Hg Cd Te)

[0086] Wavenumber resolution: 8cm -1

[0087] Accumulated count: 128

[0088] IRE: Ge

[0089] Angle of incidence: 30°

[0090] Polarizer: Wire grid, S polarization

[0091] Baseline: Wavenumber 1800–2000 cm -1 Average value of intensity in the range

[0092] Watchtower 1340cm -1 Absorption peak intensity Y at 1340 : Pachycephalus 1335–1342 cm -1 The value obtained by subtracting the baseline value from the maximum peak intensity within the range.

[0093] Wisdom 1410cm -1 Absorption peak intensity Y at 1410 : Breakwater 1400–1410 cm -1 The value obtained by subtracting the baseline value from the maximum peak intensity within the range.

[0094] The acquisition of infrared absorption spectra in 18 directions is performed by placing a sample with a polyester film exposed horizontally in a sample holder and rotating each Ge crystal placed on the sample by 10°. The angle of incidence is the angle between the perpendicular (normal) and the incident light.

[0095] In terms of improving the factor suitability of packaging materials for batteries, the surface orientation (Y max / Y minAs for ), the upper limit is less than 1.4. Regarding the upper limit, preferably about 1.3 or less may be cited, and regarding the lower limit, preferably about 1.0 or more, more preferably about 1.1 or more, and even more preferably about 1.2 or more may be cited, and regarding the preferred range, about 1.0 or more but less than 1.4, about 1.0 to 1.3, about 1.1 or more but less than 1.4, about 1.1 to 1.3, about 1.2 or more but less than 1.4, about 1.2 to 1.3, etc. The surface orientation degree (Y max / Y min By having a value of approximately 1.1 or higher, the moldability of the packaging material for batteries can be improved while improving the factor suitability.

[0096] Surface orientation as described above: Y max / Y min A polyester film having the above can be manufactured, for example, by appropriately adjusting the stretching method, stretching ratio, stretching speed, cooling temperature, heat fixing temperature, etc., when manufacturing the polyester film.

[0097] In addition, regarding the arithmetic mean roughness Ra of the polyester film layer constituting the outermost surface of the battery packaging material of the present invention, from the perspective of improving the factor suitability of the battery packaging material, the upper limit is preferably about 1000 nm or less, more preferably about 500 nm or less, the lower limit is preferably about 10 nm or more, more preferably about 20 nm or more, and the preferred range is about 10 to 1000 nm, about 20 to 500 nm.

[0098] The arithmetic mean roughness Ra of the polyester film layer constituting the outermost surface is a value obtained for the surface of the said polyester film layer in accordance with the method specified in JIS B 0601-2001. Regarding the specific measurement method, the method described in the example may be adopted. Furthermore, the measurement of the arithmetic mean roughness Ra of the polyester film layer may be performed while it is laminated onto a battery packaging material.

[0099] The arithmetic mean roughness Ra of the surface of the polyester film layer can be adjusted by the height, density, etc. of the irregularities on the surface of the cooling roll when manufacturing the polyester film. In addition, the polyester film layer may contain additives described later (flame retardants, anti-blocking agents, antioxidants, light stabilizers, tackifiers, antistatic agents, etc.) as particles, and the arithmetic mean roughness Ra may be adjusted by the particles. For example, the average particle diameter may be about 0.1 to 5 μm, and for example, the particle content may be about 0.01 to 0.1 mass%.

[0100] Specifically, the polyester constituting the polyester film layer may include, for instance, a copolymer polyester with repeating units of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, ethylene terephthalate, and a copolymer polyester with repeating units of butylene terephthalate. In addition, copolymer polyesters having ethylene terephthalate as the main repeating unit include, specifically, copolymer polyesters polymerized with ethylene isophthalate having ethylene terephthalate as the main repeating unit (hereinafter omitted according to polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / isophthalate), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), polyethylene (terephthalate / decanedicarboxylate), etc. In addition, as copolymer polyesters with butylene terephthalate as the main repeating unit, specifically, copolymer polyesters polymerized with butylene isophthalate with butylene terephthalate as the main repeating unit (hereinafter omitted depending on polybutylene(terephthalate / isophthalate)), polybutylene(terephthalate / adipate), polybutylene(terephthalate / sebacate), polybutylene(terephthalate / decanedicarboxylate), polybutylene naphthalate, etc., may be used as a single type of polyester, or two or more types may be used in combination. Polyesters have excellent heat resistance and electrolyte resistance, and have the advantage that whitening is unlikely to occur due to the adhesion of electrolyte, so they are preferably used as a material for forming the substrate layer (1).

[0101] The polyester film layer may be either an stretched polyester film or an unoriented polyester film, but from the viewpoint of preferably improving the moldability of the packaging material for batteries, it may be composed of an stretched polyester film, more preferably a biaxially stretched polyester film, and even more preferably a biaxially stretched polyethylene terephthalate film. As for the stretching method, examples include sequential biaxial stretching, inflation, and simultaneous biaxial stretching.

[0102] Although the thickness of the polyester film layer is not particularly limited, from the perspective of thinning the packaging material for batteries and improving moldability, the upper limit may be, for example, about 50 μm or less, preferably about 30 μm or less, more preferably about 25 μm or less; the lower limit may be, preferably about 1 μm or more, more preferably about 5 μm or more, further about 10 μm or more; and the preferred range may be about 1 to 50 μm, about 1 to 30 μm, about 1 to 25 μm, about 5 to 50 μm, about 5 to 30 μm, about 5 to 25 μm, about 10 to 50 μm, about 10 to 30 μm, about 10 to 25 μm.

[0103] The polyester film layer may be a single layer or a multilayer (multilayer structure). And, in the case where the polyester film layer is a multilayer, at least the polyester film located on the outermost layer side (opposite side to the barrier layer (3)) must satisfy the surface orientation degree described above, and the other polyester film is, surface orientation degree: Y max / Y min Even 1.4 or higher is acceptable.

[0104] In addition, for the purpose of improving the moldability of the packaging material for the battery, the substrate layer (1) may be formed by laminating (multilayer structuring) at least one of a resin film and a coating made of a material different from polyester on the barrier layer side of the polyester film layer in addition to the polyester film layer.

[0105] Other resin films used in the substrate layer (1) may include, for example, resin films composed of polyamide, polyolefin, epoxy resin, acrylic resin, fluoropolymer, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, and mixtures or copolymers thereof. Specific examples of a composition in which a polyester film and a resin film of a different material are laminated may include a multilayer structure in which a polyester film layer and a polyamide film layer are laminated.

[0106] As a polyamide film constituting a polyamide film layer, specifically, an aliphatic polyamide such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, or a copolymer of nylon 6 and nylon 66; an aromatic polyamide such as hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, nylon 6I6T (where I represents isophthalic acid and T represents terephthalic acid) comprising constituent units derived from terephthalic acid and / or isophthalic acid, or polyamide MXD6 (polymethoxylyleneadipamide); or an alicyclic polyamide such as polyaminomethylcyclohexyladipamide (PACM6); In addition, polyamide films may be copolymerized with lactam components or isocyanate components such as 4,4'-diphenylmethane-diisocyanate, polyesteramide copolymers or polyetheresteramide copolymers which are copolymers of copolymerized polyamide and polyester or polyalkylene ether glycol; and copolymers thereof. These polyamide films may be used as a single type or in combination of two or more types. Polyamide films have excellent stretchability and can prevent the occurrence of whitening caused by resin breakage during molding, and are preferably used as resin films used in the substrate layer (1) together with polyester films.

[0107] In the case where the substrate layer (1) is a multilayer structure of polyester film and the other resin film is provided, specific examples include a laminate of polyester film and nylon film, a laminate of multiple polyester films, and more preferably a laminate of stretched polyester film and stretched nylon film, and a laminate of multiple stretched polyester films. For example, when the substrate layer (1) is a two-layer structure, it is preferable to have a configuration in which a polyester film and a polyamide film are laminated, or a configuration in which a polyester film and a polyester film are laminated, and more preferably a configuration in which polyethylene terephthalate and nylon are laminated, or a configuration in which polyethylene terephthalate and polyethylene terephthalate are laminated. In addition, the polyester film is difficult to discolor when, for example, an electrolyte is attached to its surface, and in the battery packaging material of the present invention, the polyester film layer constitutes the outermost surface, thereby allowing for a configuration with excellent electrolyte resistance.

[0108] When the substrate layer (1) is in a multilayer structure, the thickness of the polyester film or the resin film other than the polyester film that is not located in the outermost layer can be preferably about 3 μm or more, more preferably about 5 μm or more for the lower limit, preferably about 30 μm or less, preferably about 25 μm or less for the upper limit, and for the preferred range, about 3 to 30 μm, about 3 to 25 μm, about 5 to 30 μm, or about 5 to 25 μm.

[0109] When the substrate layer (1) is formed into a multilayer structure, the polyester film or each resin film may be bonded using an adhesive, or they may be laminated directly without using an adhesive. When bonding without using an adhesive, methods of bonding in a hot-melted state, such as co-extrusion, sandwich lamination, or thermal lamination, may be used. Also, when bonding using an adhesive, the adhesive used may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the bonding mechanism of the adhesive is not particularly limited and may be any of the following: chemical reaction type, solvent volatilization type, hot-melting type, hot-pressure type, electron beam curing type, or UV curing type. Specific examples of the adhesive may include the same adhesive as exemplified in the adhesive layer (2). Also, the thickness of the adhesive may be the same as that of the adhesive layer (2).

[0110] In addition, when the substrate layer (1) has a multilayer structure, the adhesive for bonding the polyester film or each resin film preferably includes a resin composition containing a modified thermoplastic resin graft-modified with an unsaturated carboxylic acid derivative component. The modified thermoplastic resin preferably includes a resin modified with an unsaturated carboxylic acid derivative component, such as a polyolefin, a styrene-based elastomer, or a polyester-based elastomer. The resin may be used as a single type or in combination of two or more types. In addition, the unsaturated carboxylic acid derivative component may include an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, or an ester of an unsaturated carboxylic acid. The unsaturated carboxylic acid derivative component may be used as a single type or in combination of two or more types.

[0111] Examples of polyolefins in modified thermoplastic resins include low-density polyethylene, medium-density polyethylene, high-density polyethylene; ethylene-α-olefin copolymers; homo, block, or random polypropylene; propylene-α-olefin copolymers; copolymers formed by copolymerizing polar molecules such as acrylic acid and methacrylic acid with the above materials; and polymers such as cross-linked polyolefins. Polyolefins may be of a single type or a combination of two or more types.

[0112] Examples of styrene-based elastomers in modified thermoplastic resins include copolymers of styrene (hard segment) and butadiene or isoprene or hydrogenated products thereof (soft segment). Polyolefin resins may be of one type alone or a combination of two or more types.

[0113] Examples of polyester-based elastomers in modified thermoplastic resins include copolymers of crystalline polyester (hard segment) and polyalkylene ether glycol (soft segment). Polyolefins may be of one type alone or a combination of two or more types.

[0114] Examples of unsaturated carboxylic acids in modified thermoplastic resins include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, bicyclo[2,2,1]hepto-2-en-5,6-dicarboxylic acid, etc. In addition, examples of acid anhydrides of unsaturated carboxylic acids include maleic anhydride, itaconic anhydride, citraconic acid anhydride, tetrahydrophthalic anhydride, bicyclo[2,2,1]hepto-2-en-5,6-dicarboxylic acid anhydride, etc. In addition, esters of unsaturated carboxylic acids include, for example, methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethyl maleate, monomethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citraconic acid, dimethyl tetrahydrophthalate, and dimethyl bicyclo[2,2,1]hepto-2-en-5,6-dicarboxylic acid.

[0115] The above modified thermoplastic resin is obtained by heating and reacting about 0.2 to 100 parts by mass of the above unsaturated carboxylic acid derivative component with respect to 100 parts by mass of the base thermoplastic resin in the presence of a radical initiator.

[0116] The reaction temperature is preferably around 50 to 250°C, and more preferably around 60 to 200°C. The reaction time depends on the manufacturing method, but in the case of a melt graft reaction using a twin-screw extruder, it is preferably around 2 to 30 minutes within the residence time of the extruder, and more preferably around 5 to 10 minutes. In addition, the modification reaction can be carried out under either atmospheric pressure or pressurized conditions.

[0117] Organic peroxides may be used as radical initiators in the above modification reaction. Various materials can be selected as organic peroxides based on temperature conditions and reaction time, and examples include alkyl peroxides, aryl peroxides, acyl peroxides, ketone peroxides, peroxyketals, peroxycarbonates, peroxyesters, and hydroperoxides. In the case of the melt graft reaction using the aforementioned twin-screw extruder, alkyl peroxides, peroxyketals, and peroxyesters are preferred, and it is more preferable to use di-tert-butyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxy-hexine-3, and dicumyl peroxide.

[0118] When the substrate layer (1) has a multilayer structure, the thickness of the adhesive layer located between the polyester film or each resin film can preferably be about 0.1 to 5 μm, more preferably about 0.5 to 3 μm. Also, the adhesive layer may include the same coloring agent as the adhesive layer (2) described later.

[0119] In the present invention, from the perspective of improving the moldability of the packaging material for batteries, it is preferable that a lubricant be present in at least one of the interior and the surface of the polyester film layer. That is, the lubricant may be included in the polyester film layer, or the lubricant may be present on the surface of the packaging material for batteries. Furthermore, the lubricant present on the surface of the polyester film layer may be one that exudes the lubricant contained in the polyester film layer, or one that is coated on the surface of the polyester film layer.

[0120] The lubricant is not particularly limited, but preferably, amide-based lubricants and silicone-based lubricants may be used. Specific examples of the lubricant include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylolamides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid esteramides, aromatic bisamides, etc. Specific examples of saturated fatty acid amides include lauric acid amide, palmitate amide, stearate amide, behenate amide, hydroxystearate amide, etc. Specific examples of unsaturated fatty acid amides include oleate amide and erucate amide. Specific examples of substituted amides include N-oleyl palmitate amide, N-stearyl stearate amide, N-stearyl oleate amide, N-oleyl stearate amide, N-stearyl erucate amide, etc. In addition, specific examples of methylolamide include methylol stearate amide. Specific examples of saturated fatty acid bisamide include methylenebisstearate amide, ethylenebiscapric acid amide, ethylenebislauric acid amide, ethylenebisstearate amide, ethylenebishydroxystearate amide, ethylenebisbehenate amide, hexamethylenebisstearate amide, hexamethylenebisbehenate amide, hexamethylenehydroxystearate amide, N,N'-distearyladipate amide, N,N'-distearylsebacate amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylenebisolenic acid amide, ethylenebiserucic acid amide, hexamethylenebisolenic acid amide, N,N'-dioleyladipate amide, N,N'-dioleylsebacate amide, etc. Specific examples of fatty acid esteramides include stearamide ethyl stearate, etc. In addition, specific examples of aromatic bisamides include m-xylylenebisstearic acid amide, m-xylylenebishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc.In addition, as a silicone-based lubricant, non-reactive modified silicone oils such as alkyl-modified silicone oil, higher fatty acid ester-modified silicone oil, and polyether-modified silicone oil are preferred. The lubricant may be used as a single type or in combination of two or more types.

[0121] When a lubricant is present on the surface of a polyester film layer, the amount present is not particularly limited, but from the perspective of exhibiting excellent factor performance, preferably about 3 mg / m² or more, more preferably about 3 to 15 mg / m², and even more preferably about 4 to 14 mg / m². In addition, even when a lubricant is present on the surface of a polyester film layer, it is possible to measure the above infrared absorption spectrum on the surface of the polyester film layer on which the lubricant is present.

[0122] In addition, at least one of the interior and surface of the substrate layer (1) may have additives such as flame retardants, anti-blocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents. Only one type of additive may be used, or two or more types may be mixed and used.

[0123] The thickness (total thickness) of the substrate layer (1) is not particularly limited, but from the perspective of thinning the packaging material for batteries and improving moldability, the upper limit may be, for example, about 50 μm or less, preferably about 40 μm or less, and the lower limit may be, preferably about 3 μm or more, more preferably about 5 μm or more, and even more preferably about 10 μm or more, and the preferred range for the thickness of the substrate layer (1) may be about 3 to 50 μm, about 3 to 40 μm, about 5 to 50 μm, about 5 to 40 μm, about 10 to 50 μm, or about 10 to 40 μm.

[0124] [Adhesive layer (2)]

[0125] In the battery packaging material of the present invention, the adhesive layer (2) is a layer formed between the substrate layer (1) and the barrier layer (3) as needed to firmly bond them together.

[0126] The adhesive layer (2) is formed by an adhesive capable of bonding the substrate layer (1) and the barrier layer (3). The adhesive used to form the adhesive layer (2) may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the bonding mechanism of the adhesive used to form the adhesive layer (2) is not particularly limited and may be any of the following: a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressing type, etc.

[0127] Specifically, adhesive components that can be used to form the adhesive layer (2) include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolymer polyester; polyether-based adhesives; polyurethane adhesives; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, copolymer polyamides; polyolefins such as polyolefins, carboxylic acid-modified polyolefins, metal-modified polyolefins, polyvinyl acetate; cellulose-based adhesives; (meth)acrylic resins; polyimide; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; silicone-based resins, etc. These adhesive components may be used individually or in combination of two or more types. Among these adhesive components, polyurethane adhesives are preferably used.

[0128] As a polyurethane adhesive, examples include a polyurethane adhesive containing a main component (A) containing a polyol component (A) and a curing agent containing a polyisocyanate component (B), wherein the polyol component (A) contains a polyester polyol (A1), and the polyester polyol (A1) is a polyester polyol with a number average molecular weight of 5000 to 50000 composed of a polybasic acid component and a polyhydric alcohol component, wherein 45 to 95 mol% of the aromatic polybasic acid component is included among 100 mol% of the polybasic acid component, and the tensile stress when the adhesive layer is 100 kg / cm² or more and 500 kg / cm² or less. In addition, a polyurethane adhesive for battery packaging materials containing a main component and a polyisocyanate curing agent may be used, wherein the main component comprises a polyol component (A) comprising 5 to 50 weight% of a polyester polyol (A1) having a glass transition temperature of 40°C or higher and 95 to 50 weight% of a polyester polyol (A2) having a glass transition temperature of less than 40°C, and a silane coupling agent (B), and the equivalent ratio [NCO] / ([OH]+[COOH]) of the isocyanate groups included in the curing agent to the total of hydroxyl groups and carboxyl groups derived from the polyol component (A) is 1 to 30.

[0129] In addition, an adhesive may be provided that comprises one or more resins (A) selected from the group consisting of modified polypropylene and acrylic resin, or a resin containing either (A) or (B) of a coupling agent (B) containing at least one of a silane coupling agent and a titanate-based coupling agent.

[0130] Additionally, the adhesive layer (2) may include a coloring agent. By including a coloring agent in the adhesive layer (2), the packaging material for batteries can be colored. Known materials such as pigments and dyes may be used as coloring agents. Additionally, only one type of coloring agent may be used, or two or more types may be mixed and used.

[0131] For example, specific examples of inorganic pigments include preferably carbon black, titanium oxide, etc. In addition, specific examples of organic pigments include preferably azo pigments, phthalocyanine pigments, condensed polycyclic pigments, etc. Examples of azo pigments include soluble pigments such as watching red and carmine 6C; and insoluble azo pigments such as monoazo yellow, disazo yellow, pyrazolone orange, pyrazolone red, and permanent red. Examples of phthalocyanine pigments include copper phthalocyanine pigments and blue or green pigments as non-metallic phthalocyanine pigments. Examples of condensed polycyclic pigments include dioxazine violet and quinacridone violet. In addition, pearl pigments and fluorescent pigments may also be used as pigments.

[0132] Among coloring agents, carbon black is preferred, for example, to make the appearance of battery packaging materials black.

[0133] The average particle diameter of the pigment is not particularly limited, and for example, it can be about 0.05 to 5 μm, preferably about 0.08 to 2 μm. In addition, the average particle diameter of the pigment is the median diameter measured by a laser diffraction / scattering particle diameter distribution measuring device.

[0134] The pigment content in the adhesive layer (2) is not particularly limited when the battery packaging material is colored, and for example, about 5 to 60 mass% can be used.

[0135] As for the thickness of the adhesive layer (2), it is not particularly limited as long as it functions as an adhesive layer, but for example, about 1 to 10 μm, preferably about 2 to 5 μm.

[0136] [Color layer]

[0138] The coloring layer is a layer formed as needed between the substrate layer (1) and the adhesive layer (2) (not shown). By forming the coloring layer, the packaging material for the battery can be colored.

[0139] The colored layer can be formed, for example, by applying an ink containing a coloring agent to the surface of the substrate layer (1) or the surface of the barrier layer (3). Known coloring agents such as pigments and dyes may be used. Additionally, only one type of coloring agent may be used, or two or more types may be mixed and used.

[0140] Specific examples of coloring agents included in the coloring layer are those identical to those exemplified in the [adhesive layer (2)] column.

[0141] [Barrier layer (3)]

[0142] In a packaging material for a battery, the barrier layer (3) is a layer that, in addition to improving the strength of the packaging material for the battery, has the function of preventing water vapor, oxygen, light, etc. from entering the battery. The barrier layer (3) can be formed by a metal foil, a metal deposition film, an inorganic oxide deposition film, a carbon-containing inorganic oxide deposition film, a film formed by these deposition layers, etc., and it is preferable that the layer be formed of metal. Specifically, the metal constituting the barrier layer (3) may be aluminum, stainless steel, titanium steel, etc., and preferably aluminum or stainless steel. It is preferable that the barrier layer (3) be formed by a metal foil, and it is even more preferable that it be formed by an aluminum alloy foil or a stainless steel foil.

[0143] In order to prevent wrinkles or pinholes from occurring in the barrier layer (3) during the manufacture of packaging materials for batteries, it is more preferable that the barrier layer be formed by a soft aluminum foil, such as, for example, annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O).

[0144] In addition, examples of stainless steel sheets include austenitic stainless steel sheets and ferritic stainless steel sheets. It is preferable that the stainless steel sheet be composed of austenitic stainless steel.

[0145] Specific examples of austenitic stainless steel constituting the stainless steel sheet include SUS304, SUS301, SUS316L, etc., and among these, SUS304 is particularly preferred.

[0146] The thickness of the barrier layer (3) is not particularly limited as long as it functions as a barrier layer against water vapor, etc. However, from the perspective of thinning the thickness of the packaging material for the battery, the upper limit can preferably be about 85 μm or less, more preferably about 50 μm or less, and even more preferably 45 μm or less, and the lower limit can preferably be about 10 μm or more, and the range of the thickness can be, for example, about 10 to 85 μm, preferably about 10 to 50 μm, and more preferably about 10 to 45 μm. And, when the barrier layer (3) is composed of stainless steel foil, the thickness of the stainless steel foil can be preferably about 85 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, even more preferably about 30 μm or less, particularly preferably about 25 μm or less, and the lower limit can be about 10 μm or more, and the preferred thickness range can be about 10 to 85 μm, about 10 to 50 μm, more preferably about 10 to 40 μm, more preferably about 10 to 30 μm, and even more preferably about 15 to 25 μm.

[0147] In addition, for the stabilization of adhesion and prevention of dissolution or corrosion, it is desirable that at least one side, preferably both sides, of the barrier layer (3) be chemically treated. Here, chemical treatment refers to a treatment that forms an acid-resistant film on the surface of the barrier layer. When an acid-resistant film is formed on the surface of the barrier layer (3) of the present invention, the barrier layer (3) includes an acid-resistant film. Examples of chemical treatments include chromate treatment using chromate compounds such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium hydroxide, chromium phosphate, acetylacetate chromate, chromium chloride, and potassium chromium sulfate; chromate treatment using phosphate compounds such as sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphate; and chromate treatment using an amino phenol polymer having repeating units represented by the following general formulas (1) to (4). In addition, in the aminified phenol polymer, the repeating unit represented by the following general formulas (1) to (4) may be included as a single type, or two or more types may be any combination.

[0148]

[0149]

[0150]

[0151]

[0152] In general formulas (1) to (4), X represents a hydrogen atom, a hydroxyl group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. Also, R 1 and R 2 Each represents a hydroxyl group, an alkyl group, or a hydroxyalkyl group, and is the same or different. In general formulas (1) to (4), X, R 1 and R 2Examples of alkyl groups represented by include straight-chain or branched-chain alkyl groups having 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl groups. In addition, X and R 1 and R 2 As the hydroxyalkyl group represented by, for example, a straight-chain or branched-chain alkyl group having 1 to 4 carbon atoms substituted with one hydroxyl group, such as a hydroxymethyl group, 1-hydroxyethyl group, 2-hydroxyethyl group, 1-hydroxypropyl group, 2-hydroxypropyl group, 3-hydroxypropyl group, 1-hydroxybutyl group, 2-hydroxybutyl group, 3-hydroxybutyl group, or 4-hydroxybutyl group, may be provided. In general formulas (1) to (4), X, R 1 and R 2 The alkyl group and the hydroxyalkyl group represented by may be the same or different. In general formulas (1) to (4), X is preferably a hydrogen atom, a hydroxyl group, or a hydroxyalkyl group. The number average molecular weight of the aminified phenol polymer having repeating units represented by general formulas (1) to (4) is, for example, preferably 5 to 1 million, and more preferably 1,000 to 20,000.

[0153] In addition, as a chemical treatment method to impart corrosion resistance to the barrier layer (3), a method may be used to form an acid-resistant film on the surface of the barrier layer (3) by coating a substance in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate, are dispersed in phosphoric acid, and then performing baking treatment at 150°C or higher. Furthermore, a resin layer may be further formed on the acid-resistant film by crosslinking a cationic polymer with a crosslinking agent. Here, examples of cationic polymers include polyethyleneimine, an ionic polymer complex composed of polyethyleneimine and a carboxylic acid, a primary amine graft acrylic resin in which a primary amine is graft-polymerized onto an acrylic main frame, polyallylamine or its derivative, aminophenol, etc. As for these cationic polymers, only one type may be used, or two or more types may be used in combination. In addition, examples of crosslinking agents include compounds having at least one functional group selected from the group consisting of isocyanate groups, glycidyl groups, carboxyl groups, and oxazoline groups, silane coupling agents, etc. As for these crosslinking agents, only one type may be used, or two or more types may be used in combination.

[0154] In addition, as a specific method for forming an acid-resistant film, for example, at least the inner layer side surface of an aluminum foil (barrier layer) is first degreased using a well-known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the acid-resistant film can be formed by applying a treatment solution (aqueous solution) to the degreased surface using a well-known coating method such as a roll coating method, a gravure printing method, or an immersion method, with a treatment solution (aqueous solution) mainly composed of metal phosphate salts such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, and Zn (zinc) phosphate, and a mixture of these metal salts, or a treatment solution (aqueous solution) mainly composed of non-metal phosphate salts and a mixture of these non-metal salts, or a treatment solution (aqueous solution) composed of these and a water-based synthetic resin such as acrylic resin, phenolic resin, or polyurethane. For example, in the case of treatment with a Cr(chromium) phosphate salt-based treatment solution, CrPO4 (chromium phosphate), AlPO4 (aluminum phosphate), Al2O3 (aluminum oxide), and Al(OH) x It forms an acid-resistant coating composed of (aluminum hydroxide), AlFx (aluminum fluoride), etc., and when treated with a Zn (zinc) phosphate salt-based treatment solution, Zn2PO4·4H2O (zinc phosphate hydrate), AlPO4 (aluminum phosphate), Al2O3 (aluminum oxide), Al(OH) x (Aluminum hydroxide), AlF x It becomes an acid-resistant coating made of (aluminum fluoride), etc.

[0155] In addition, as another example of a specific method for forming an acid-resistant film, for instance, at least the inner layer side of the aluminum foil can be degreased first by a well-known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then a well-known anodic oxidation treatment can be performed on the degreased surface to form an acid-resistant film.

[0156] In addition, other examples of acid-resistant coatings include coatings of phosphorus compounds (e.g., phosphate-based) and chromium compounds (chromate-based). Examples of phosphate-based compounds include zinc phosphate, iron phosphate, manganese phosphate, calcium phosphate, and chromium phosphate, while examples of chromate-based compounds include chromium chromate.

[0157] In addition, as another example of an acid-resistant film, by forming an acid-resistant film such as a phosphate, chromate, fluoride, or triazine thiol compound, it prevents delamination between the aluminum and the substrate layer during embossing, prevents dissolution and corrosion of the aluminum surface due to hydrogen fluoride generated from the reaction between the electrolyte and moisture, and especially prevents dissolution and corrosion of aluminum oxide present on the aluminum surface, and also improves the adhesion (wetting) of the aluminum surface, prevents delamination between the substrate layer and aluminum during heat sealing, and in the case of an embossing type, prevents delamination between the substrate layer and aluminum during press forming. Among the materials forming the acid-resistant film, an aqueous solution composed of three components of phenol resin, chromium fluoride (III) compound, and phosphoric acid is applied to the aluminum surface, and the drying and baking process is good.

[0158] In addition, the acid-resistant film comprises a layer having cerium oxide, phosphoric acid or phosphate, an anionic polymer, and a crosslinking agent that crosslinks the anionic polymer, wherein the phosphoric acid or phosphate may be formulated in an amount of 1 to 100 parts by mass per 100 parts by mass of cerium oxide. It is preferable that the acid-resistant film has a multilayer structure further comprising a cationic polymer and a layer having a crosslinking agent that crosslinks the cationic polymer.

[0159] In addition, it is preferable that the above anionic polymer is poly(meth)acrylic acid or its salt, or a copolymer having (meth)acrylic acid or its salt as a main component. In addition, it is preferable that the above crosslinking agent is at least one selected from the group consisting of a compound having a functional group among isocyanate groups, glycidyl groups, carboxyl groups, and oxazoline groups, and a silane coupling agent.

[0160] In addition, it is preferable that the above phosphoric acid or phosphate is a condensed phosphoric acid or a condensed phosphate.

[0161] The phosphating treatment may be performed using only one type of phosphating treatment or by combining two or more types of phosphating treatments. Furthermore, these phosphating treatments may be performed using one type of compound alone or by combining two or more types of compounds. Among the phosphating treatments, chromate treatment of chromate or chromate treatment combining a chromate compound, a phosphate compound, and an amino phenol polymer is preferred.

[0162] Specific examples of acid-resistant coatings include those comprising at least one of phosphorus compounds (phosphates, etc.), chromium compounds (chromates), fluorides, and triazinethiol compounds. Additionally, acid-resistant coatings comprising cerium compounds are also preferred. As for the cerium compound, cerium oxide is preferred.

[0163] In addition, specific examples of acid-resistant coatings include phosphate-based coatings, chromate-based coatings, fluoride-based coatings, and triazinethiol compound coatings. As an acid-resistant coating, it may be any one of these types or a combination of multiple types. Furthermore, as an acid-resistant coating, it may be formed by a treatment solution consisting of a mixture of a metal phosphate salt and a water-based synthetic resin, or a treatment solution consisting of a mixture of a non-metal phosphate salt and a water-based synthetic resin, after degreasing the chemically treated surface of the barrier layer.

[0164] In addition, the composition analysis of the acid-resistant film can be performed, for example, using time-of-flight secondary ion mass spectrometry. By analyzing the composition of the acid-resistant film using time-of-flight secondary ion mass spectrometry, for example, secondary ions consisting of Ce, P, and O (for example, Ce2PO4) + , CePO4 - At least one of the following) or, for example, a secondary ion composed of Cr, P, and O (for example, CrPO2 + , CrPO4 - A peak originating from at least one of the following is detected.

[0165] Although there is no particular limitation on the amount of acid-resistant film formed on the surface of the barrier layer (3) during the chemical treatment, for example, if the above chromate treatment is performed, it is preferable that the chromate compound is contained in an amount of about 0.5 to 50 mg in chromium equivalent, preferably about 1.0 to 40 mg, the phosphorus compound is contained in an amount of about 0.5 to 50 mg in chromium equivalent, preferably about 1.0 to 40 mg, and the amino phenol polymer is contained in an amount of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, per 1 m² of the surface of the barrier layer (3).

[0166] Although there is no particular limitation on the thickness of the acid-resistant film, in terms of the cohesiveness of the film or the adhesion to the barrier layer or the heat-sealable resin layer, it is preferably about 1 nm to 20 μm, more preferably about 1 to 100 nm, and even more preferably about 1 to 50 nm. In addition, the thickness of the acid-resistant film can be measured by observation using a transmission electron microscope, or by a combination of observation using a transmission electron microscope and energy-dispersive X-ray spectroscopy or electron beam energy loss spectroscopy.

[0167] Chemical conversion treatment is performed by applying a solution containing a compound used for forming an acid-resistant film to the surface of a barrier layer by bar coating, roll coating, gravure coating, immersion, etc., and then heating the barrier layer to a temperature of 70 to 200°C. In addition, before performing chemical conversion treatment on the barrier layer, the barrier layer may be subjected to degreasing treatment by alkaline immersion, electrolytic cleaning, acid cleaning, electrolytic acid cleaning, etc. By performing degreasing treatment in this manner, it becomes possible to perform chemical conversion treatment on the surface of the barrier layer more efficiently.

[0168] [Thermal fusion resin layer (4)]

[0169] In the packaging material for a battery according to the present invention, the heat-fusible resin layer (4) corresponds to the innermost layer and is a layer that seals the battery element by heat-fusible resin layers together during assembly of the battery.

[0170] Regarding the resin component used in the heat-fusible resin layer (4), it is not particularly limited to those that are heat-fusible, but examples include polyolefin, cyclic polyolefin, carboxylic acid modified polyolefin, and carboxylic acid modified cyclic polyolefin. That is, the resin constituting the heat-fusible resin layer (4) may or may not contain a polyolefin backbone, but it is preferable that it contains a polyolefin backbone. Whether the resin constituting the heat-fusible resin layer (4) contains a polyolefin backbone can be analyzed, for example, by infrared spectroscopy, gas chromatography-mass spectrometry, etc., and the analysis method does not particularly matter. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, the wavenumber is 1760 cm⁻¹. -1 Nearby and Watchtower 1780cm -1 A peak originating from maleic anhydride is detected in the vicinity. However, if the degree of acid modification is low, the peak may become small and not be detected. In such cases, analysis is possible using nuclear magnetic resonance spectroscopy.

[0171] Specifically, the above polyolefins may include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); and terpolymers of ethylene-butene-propylene. Among these polyolefins, polyethylene and polypropylene are preferably used.

[0172] The above-mentioned cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of olefins that are constituent monomers of the above-mentioned cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, isoprene, etc. In addition, examples of cyclic monomers that are constituent monomers of the above-mentioned cyclic polyolefin include cyclic alkenes such as norbornene; specifically, examples of cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norvonadiene. Among these polyolefins, cyclic alkenes are preferably, and more preferably norbornene is used. Additionally, styrene may be used as a constituent monomer.

[0173] The above-mentioned carboxylic acid modified polyolefin is a polymer modified by block polymerization or graft polymerization of the above-mentioned polyolefin with a carboxylic acid. Examples of carboxylic acids used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, itaconic anhydride, etc.

[0174] The above-mentioned carboxylic acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a portion of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, or by block polymerization or graft polymerization of an α,β-unsaturated carboxylic acid or its anhydride with respect to the cyclic polyolefin. The carboxylic acid-modified cyclic polyolefin is the same as that described above. Furthermore, the carboxylic acid used for modification is the same as that used for modifying the polyolefin.

[0175] Among these resin components, preferably carboxylic acid modified polyolefin; more preferably carboxylic acid modified polypropylene may be used.

[0176] The heat-fusible resin layer (4) may be formed by a single resin component alone, or by a blend polymer combining two or more resin components. Additionally, the heat-fusible resin layer (4) may be formed as a single layer, but may also be formed as two or more layers by the same or different resin components.

[0177] A lubricant may be included in the heat-fusible resin layer (4). Additionally, the lubricant present on the surface of the heat-fusible resin layer (4) may be a lubricant exuded from the resin constituting the heat-fusible resin layer (4), or a lubricant applied to the surface of the heat-fusible resin layer (4). When the heat-fusible resin layer (4) contains a lubricant, the moldability of the battery packaging material can be improved. The lubricant is not particularly limited and known lubricants may be used, for example, those exemplified in the substrate layer (1) above. The lubricant may be used as a single type or in combination of two or more types. The amount of lubricant present on the surface of the heat-fusible resin layer (4) is not particularly limited, but from the perspective of improving the moldability of the electronic packaging material, it is preferably about 10 to 50 mg / m², and more preferably about 15 to 40 mg / m².

[0178] In addition, the thickness of the heat-fusible resin layer (4) is not particularly limited as long as it functions as a heat-fusible resin layer, but for example, it can be about 100 μm or less, preferably about 85 μm or less, more preferably about 15 to 85 μm. And, for example, when the thickness of the adhesive layer (5) described later is 10 μm or more, the thickness of the heat-fusible resin layer (4) can be about 85 μm or less, more preferably about 15 to 65 μm, and for example, when the thickness of the adhesive layer (5) described later is less than 10 μm or when the adhesive layer (5) is not formed, the thickness of the heat-fusible resin layer (4) can be about 20 μm or more, more preferably about 35 to 85 μm.

[0179] [Adhesive layer (5)]

[0180] In the battery packaging material of the present invention, the adhesive layer (5) is a layer formed between the barrier layer (3) and the heat-fusible resin layer (4) as needed to firmly bond them together.

[0181] The adhesive layer (5) is formed by a resin capable of bonding the barrier layer (3) and the heat-fusible resin layer (4). As for the resin used to form the adhesive layer (5), the adhesive mechanism and the type of adhesive component may be the same as the adhesive exemplified in the adhesive layer (2). Additionally, as for the resin used to form the adhesive layer (5), polyolefins such as polyolefin, cyclic polyolefin, carboxylic acid modified polyolefin, and carboxylic acid modified cyclic polyolefin exemplified in the aforementioned heat-fusible resin layer (4) may also be used. From the perspective of excellent adhesion between the barrier layer (3) and the heat-fusible resin layer (4), carboxylic acid modified polyolefin is preferred as the polyolefin, and carboxylic acid modified polypropylene is particularly preferred. That is, the resin constituting the adhesive layer (5) may or may not include a polyolefin backbone, but it is preferable that it includes a polyolefin backbone. Whether the resin constituting the adhesive layer (5) contains a polyolefin framework can be analyzed, for example, by infrared spectroscopy, gas chromatography mass spectrometry, etc., and the analysis method does not particularly matter. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, the wavenumber is 1760 cm -1 Nearby and Watchtower 1780cm -1 A peak derived from maleic anhydride is detected in the vicinity. However, if the degree of acid modification is low, the peak may become small and not be detected. In such cases, analysis is possible using nuclear magnetic resonance spectroscopy.

[0182] In order to improve the adhesion between the barrier layer (3) (or acid-resistant film) and the heat-sealable resin layer (4), it is preferable that the adhesive layer (5) includes an acid-modified polyolefin. The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component such as a carboxylic acid. Examples of acid components used for modification include carboxylic acids or their anhydrides such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride. Additionally, examples of polyolefins to be modified include polyethylene such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylene such as homopolypropylene, block copolymer of polypropylene (e.g., block copolymer of propylene and ethylene), and random copolymer of polypropylene (e.g., random copolymer of propylene and ethylene); and terpolymer of ethylene-butene-propylene. Among these polyolefins, preferably polyethylene and polypropylene can be cited.

[0183] In the adhesive layer (5), among acid-modified polyolefins, maleic anhydride-modified polyolefin, and furthermore maleic anhydride-modified polypropylene are preferred.

[0184] In addition, from the perspective of making a battery packaging material that has excellent shape stability after molding while keeping the thickness of the battery packaging material thin, it is more preferable that the adhesive layer (5) is a cured product of a resin composition comprising an acid-modified polyolefin and a curing agent. As for the acid-modified polyolefin, the above-mentioned example may be preferably exemplified.

[0185] Additionally, the adhesive layer (5) is preferably a cured product of a resin composition comprising at least one selected from the group consisting of an acid-modified polyolefin and a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition comprising at least one selected from the group consisting of an acid-modified polyolefin and a compound having an isocyanate group and a compound having an epoxy group. Additionally, the adhesive layer (5) is preferably a cured product of a resin composition comprising at least one selected from the group consisting of a urethane resin, an ester resin, and an epoxy resin, and is more preferably a cured product of a urethane resin and an epoxy resin. As for the ester resin, an amide ester resin is preferred, for example. An amide ester resin is generally produced by the reaction of a carboxyl group and an oxazoline group. The adhesive layer (5) is more preferably a cured product of a resin composition comprising at least one of these resins and the acid-modified polyolefin. And, if unreacted material of a curing agent such as a compound having an isocyanate group, a compound having an oxazoline group, or an epoxy resin remains in the adhesive layer (5), the presence of unreacted material can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS).

[0186] In addition, in order to further enhance the adhesion between the barrier layer (3) (or acid-resistant film), the heat-fusible resin layer (4), and the adhesive layer (5), the adhesive layer (5) is preferably a cured product of a resin composition comprising at least one curing agent selected from the group consisting of oxygen atoms, heterocyclic rings, C=N bonds, and COC bonds. Examples of curing agents having heterocyclic rings include curing agents having oxazoline groups, curing agents having epoxy groups, etc. Also, examples of curing agents having C=N bonds include curing agents having oxazoline groups, curing agents having isocyanate groups, etc. Additionally, examples of curing agents having COC bonds include curing agents having oxazoline groups, curing agents having epoxy groups, urethane resins, etc. It can be confirmed that the adhesive layer (5) is a cured product of a resin composition containing these curing agents, for example, by methods such as gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), and X-ray photoelectron spectroscopy (XPS).

[0187] Compounds having isocyanate groups are not particularly limited, but from the perspective of effectively increasing the adhesion between the acid-resistant film and the adhesive layer (5), polyfunctional isocyanate compounds are preferably used. Polyfunctional isocyanate compounds are not particularly limited as long as they are compounds having two or more isocyanate groups. Specific examples of polyfunctional isocyanate curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurate-ized versions thereof, mixtures thereof, or copolymers with other polymers.

[0188] The content of the compound having an isocyanate group in the adhesive layer (5) is preferably in the range of 0.1 to 50 mass% in the resin composition constituting the adhesive layer (5), and more preferably in the range of 0.5 to 40 mass%.

[0189] Compounds having an oxazoline group are not particularly limited as long as they have an oxazoline backbone. Specific examples of compounds having an oxazoline group include those having a polystyrene main chain or an acrylic main chain. In addition, commercially available products include, for example, the Epochros series manufactured by Nippon Shokubai Co., Ltd.

[0190] In the adhesive layer (5), the ratio of the compound having an oxazoline group is preferably in the range of 0.1 to 50 mass% in the resin composition constituting the adhesive layer (5), and more preferably in the range of 0.5 to 40 mass%. By doing so, the adhesion between the barrier layer (3) (or acid-resistant film) and the adhesive layer (5) can be effectively increased.

[0191] As for the epoxy resin, any known epoxy resin is not particularly limited and can be used as long as it is a resin capable of forming a cross-linked structure by epoxy groups present within the molecule. The weight-average molecular weight of the epoxy resin is preferably 50 to 2000, more preferably 100 to 1000, and even more preferably 200 to 800. Furthermore, in the present invention, the weight-average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.

[0192] Specific examples of epoxy resins include trimethylolpropane glycidyl ether derivatives, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolak glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resin may be used alone or in combination of two or more types.

[0193] In the adhesive layer (5), the ratio of epoxy resin is preferably in the range of 0.1 to 50 mass% among the resin composition constituting the adhesive layer (5), and more preferably in the range of 0.5 to 40 mass%. This allows the adhesion between the barrier layer (3) (or acid-resistant film) and the adhesive layer (5) to be effectively increased.

[0194] In addition, in the present invention, when the adhesive layer (5) is a cured product of a resin composition comprising at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as the main component, and the compound having an isocyanate group, the compound having an oxazoline group, and the epoxy resin each function as a curing agent.

[0195] The carbodiimide curing agent is not particularly limited as long as it is a compound having at least one carbodiimide group (-N=C=N-). As a carbodiimide curing agent, a polycarbodiimide compound having at least two carbodiimide groups is preferred.

[0196] In terms of improving the adhesion between the barrier layer (3) and the heat-fusible resin layer (4) by the adhesive layer (5), the curing agent may be composed of two or more types of compounds.

[0197] The content of the curing agent in the resin composition forming the adhesive layer (5) is preferably in the range of about 0.1 to 50 mass%, more preferably in the range of about 0.1 to 30 mass%, and even more preferably in the range of about 0.1 to 10 mass%.

[0198] In addition, the adhesive layer (5) can also preferably be formed using an adhesive, for example. As an adhesive, for example, it may be formed from an adhesive composition containing an amorphous polyolefin resin (A) having carboxyl groups, a polyfunctional isocyanate compound (B), and a tertiary amine (C) that does not have a functional group reacting with the polyfunctional isocyanate compound (B), containing the polyfunctional isocyanate compound (B) in a range where the amount of isocyanate groups is 0.3 to 10 moles per 1 mole of total carboxyl groups, and containing the tertiary amine (C) in a range where the amount of total carboxyl groups is 1 to 10 moles per 1 mole of total carboxyl groups. In addition, as an adhesive, it comprises a styrene-based thermoplastic elastomer (A), a tackifier (B), and a polyisocyanate (C), wherein, in 100 weight% of the total of the styrene-based thermoplastic elastomer (A) and the tackifier (B), the styrene-based thermoplastic elastomer (A) comprises 20 to 90 weight% and the tackifier (B) comprises 10 to 80 weight%, wherein the styrene-based thermoplastic elastomer (A) has active hydrogen derived from amino groups or hydroxyl groups at a concentration of 0.003 to 0.04 mmol / g, and for every 1 mole of the active hydrogen derived from the styrene-based thermoplastic elastomer (A), the active hydrogen derived from the functional groups of the tackifier (B) comprises 0 to 15 moles, and the polyisocyanate (C) comprises the styrene-based thermoplastic Examples include those formed by an adhesive composition in which isocyanate groups are included in a range of 3 to 150 moles per 1 mole of the total of active hydrogen derived from the elastomer (A) and active hydrogen derived from the tackifier (B).

[0199] Regarding the thickness of the adhesive layer (5), it is not particularly limited as long as it functions as an adhesive layer, but for example, about 50 μm or less, about 40 μm or less, preferably about 30 μm or less, more preferably about 20 μm or less, and even more preferably about 5 μm or less, as a lower limit, about 0.1 μm or more, about 0.5 μm or more, about 10 μm or more, and as a range of thickness, preferably, about 0.1 to 50 μm, about 0.1 to 40 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 to 5 μm, about 0.5 to 50 μm, about 0.5 to 40 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, about 0.5 to 5 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 20 μm. More specifically, if the adhesive exemplified in the adhesive layer (2) is used, the thickness can preferably be 2 to 10 μm, more preferably 2 to 5 μm. Also, if the resin exemplified in the heat-fusible resin layer (4) is used, the thickness can preferably be 2 to 50 μm, more preferably 10 to 40 μm. Additionally, if it is a cured product of an acid-modified polyolefin and a curing agent, the thickness can preferably be about 30 μm or less, more preferably about 0.1 to 20 μm, and even more preferably about 0.5 to 5 μm. If the adhesive layer is formed by the adhesive composition described above, the thickness after drying and curing can be about 1 to 30 g / m². And, if the adhesive layer (5) is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer (5) can be formed by applying the said resin composition and curing it by heating, etc.

[0200] As described below, in the manufacture of a laminate constituting the battery packaging material of the present invention, a method of laminating an adhesive layer (5) and a heat-fusible resin layer (4) on a barrier layer (3) in this order may be adopted by laminating the adhesive layer (5) and the heat-fusible resin layer (4) on the barrier layer (3) by co-extrusion. That is, in the battery packaging material of the present invention, the adhesive layer and the heat-fusible resin layer may be a co-extruded laminate.

[0201] 3. Method for manufacturing packaging materials for batteries

[0202] The method for manufacturing a battery packaging material according to the present invention is not particularly limited as long as a laminate is obtained by laminating each layer of a predetermined composition. As a method for manufacturing a battery packaging material, for example, it includes a process of obtaining a laminate by laminating, for at least, a substrate layer located on the outermost surface, a barrier layer, and a heat-sealable resin layer in this order, wherein the outermost surface of the substrate layer is composed of a polyester film layer, and furthermore, as a polyester film, when infrared absorption spectra are acquired in 18 directions in 10° increments from 0° to 180° on the surface of the polyester film using the total internal reflection method of Fourier transform infrared spectroscopy, the 1340 cm⁻¹ of these infrared absorption spectra -1 Absorption peak intensity Y at 1340 and, 1410cm -1 Absorption peak intensity Y at 1410 The ratio of (Y 1340 / Y 1410 Maximum value Y of ) max and minimum value Y min Ratio of (surface orientation: Y max / Y min One method to use is to utilize values ​​less than 1.4.

[0203] An example of a method for manufacturing a battery packaging material according to the present invention is as follows. First, a laminate (hereinafter also referred to as “Laminate A”) is formed in which a substrate layer (1), an adhesive layer (2), and a barrier layer (3) are laminated in order. Specifically, the formation of the laminate A can be carried out by a dry lamination method in which an adhesive used for forming the adhesive layer (2) is applied and dried on the substrate layer (1) or, if necessary, on the barrier layer (3) whose surface has been chemically treated, using a coating method such as a gravure coating method or a roll coating method, and then the barrier layer (3) or the substrate layer (1) is laminated to cure the adhesive layer (2).

[0204] Next, an adhesive layer (5) and a heat-fusible resin layer (4) are laminated on the barrier layer (3) of laminate A in this order. For example, (1) a method of laminating an adhesive layer (5) and a heat-fusible resin layer (4) by co-extruding them onto a barrier layer (3) of laminate A (co-extrusion lamination method), (2) a method of separately forming a laminate in which an adhesive layer (5) and a heat-fusible resin layer (4) are laminated, and laminating this onto a barrier layer (3) of laminate A by a thermal lamination method, (3) a method of laminating an adhesive to form an adhesive layer (5) onto a barrier layer (3) of laminate A by extrusion or solution coating, drying at a high temperature, and baking, and laminating a heat-fusible resin layer (4) that has been pre-made in a sheet form onto the adhesive layer (5) by a thermal lamination method, (4) a method of inserting a molten adhesive layer (5) along the barrier layer (3) of laminate A and a heat-fusible resin layer (4) that has been pre-made in a sheet form, and through the adhesive layer (5) laminate A and heat-fusible Methods such as joining resin layers (4) (sandwich laminate method) can be used.

[0205] As described above, a laminate is formed comprising a substrate layer (1), an adhesive layer (2) formed as needed, a barrier layer (3) with a surface chemically treated as needed, an adhesive layer (5), and a heat-fusible resin layer (4). However, to strengthen the adhesion of the adhesive layer (2) or the adhesive layer (5), further heat treatment such as a hot roll contact type, a hot air type, a near-infrared type, or a far-infrared type may be provided. As for the conditions of such heat treatment, for example, 1 to 5 minutes at about 150 to 250°C.

[0206] In the battery packaging material of the present invention, each layer constituting the laminate may, if necessary, undergo surface activation treatments such as corona treatment, blast treatment, oxidation treatment, or ozone treatment in order to improve or stabilize film formation properties, lamination processing, and suitability for secondary processing of the final product (pouching, embossing).

[0207] 4. Uses of packaging materials for batteries

[0208] The battery packaging material of the present invention is used in a packaging body for sealing and accommodating battery elements such as a positive electrode, a negative electrode, and an electrolyte. That is, a battery element having at least a positive electrode, a negative electrode, and an electrolyte can be accommodated within a packaging body formed by the battery packaging material of the present invention to form a battery. The battery packaging material of the present invention is suitable for use in applications where printing is performed on the surface of a polyester film layer located on the outermost surface.

[0209] Specifically, a battery element comprising at least a positive electrode, a negative electrode, and an electrolyte is covered with the battery packaging material of the present invention such that a flange portion (an area where heat-sealable resin layers come into contact) is formed on the peripheral edge of the battery element while a metal terminal connected to each of the positive electrode and the negative electrode protrudes outward, and the heat-sealable resin layers of the flange portion are heat-sealed to seal the battery, thereby providing a battery using the battery packaging material. Furthermore, when the battery element is contained within a packaging body formed by the battery packaging material of the present invention, the heat-sealable resin portion of the battery packaging material of the present invention is positioned on the inside (a surface in contact with the battery element) to form the packaging body. Additionally, the infrared absorption spectrum and the arithmetic mean roughness Ra on the surface of the polyester film layer can be measured by obtaining the battery packaging material from the battery and measuring the polyester film layer of the obtained battery packaging material. However, the measurement of the infrared absorption spectrum and the arithmetic mean roughness Ra regarding the battery packaging material obtained from the battery is performed, respectively, on the battery packaging material of a part different from the surrounding edge flange (the part where the heat-sealable resin layers are heat-sealable together) or the side part (preferably, the top or bottom surface of the battery).

[0210] In the present invention, a battery having printing performed on the surface of a polyester film layer can be manufactured by a method comprising: a receiving process of receiving a battery element having at least a positive electrode, a negative electrode, and an electrolyte within a packaging body formed by the battery packaging material of the present invention; and a process of performing printing on the surface of a polyester film layer located on the outermost surface at least before and after the receiving process. That is, the battery of the present invention may be a battery having a printed portion on its surface. A printed portion is a part formed on the surface of the battery in which a barcode, pattern, character, symbol, etc., is printed.

[0211] In the battery packaging material of the present invention, when the printing suitability of the polyethylene terephthalate film surface is evaluated under the following conditions, the radius of the dot forming the printing portion is preferably 130 μm or more, 135 μm or more, 140 μm or more, 151 μm or less, and 149 μm or less. Preferred ranges for the radius include approximately 130 to 151 μm, approximately 130 to 149 μm, approximately 135 to 151 μm, approximately 135 to 149 μm, approximately 140 to 151 μm, and approximately 140 to 149 μm. By satisfying such values ​​for the radius of the dot, the printing suitability can be evaluated as excellent. Specifically, printing such as barcodes, patterns, characters, and symbols is formed by an aggregation of ink dots, and if the radius of the dot forming the printing portion satisfies the above values, the radius of the dot is not excessively small or excessively large, and the desired printing can be appropriately performed.

[0212] In addition, in the packaging material for batteries according to the present invention, when the printing suitability of the polyethylene terephthalate film surface is evaluated under the following conditions, it is preferable that the circularity of the dot forming the printing portion is 0.725 or higher. The closer the circularity of the printing portion is to 1, the better the printing suitability can be evaluated. Specifically, for printing such as barcodes, patterns, characters, and symbols, if the circularity of the dot forming the printing portion satisfies the above value, the shape of the dot is not distorted, and the desired printing can be performed appropriately.

[0213] <Evaluation of the surface properties of polyethylene terephthalate films>

[0214] In an environment with a temperature of 24°C and a relative humidity of 50%, ink is applied to the surface of the polyethylene terephthalate film of each battery packaging material prepared above using an inkjet printer (Markem Image 9040 (1.1M head) manufactured by Markem Image Co., Ltd.) and dried for 10 seconds. Next, the printability of the polyethylene terephthalate film surface is evaluated based on the radius and circularity of the dots of the printed area formed on the surface of the polyethylene terephthalate film. The printing setting conditions are set as follows: ink viscosity: 3.4 cps, temperature: 34°C, pressure: 270 bar, nozzle size: diameter 50 μm, resolution (dot density): 115 dpi. The method for determining the radius and circularity of the dots of the printed area is as described below. The above evaluation is performed in the state of the battery packaging material. In addition, the radius and circularity of the dots of the printed area are taken as average values ​​with a number of 3. Also, when performing the evaluation, operations such as wiping the surface of the polyethylene terephthalate film are not performed.

[0215] The distance between the inkjet printer print head and the surface of the polyethylene terephthalate film is set to 20 mm, and 5157E standard ink is used.

[0216] In addition, to observe the radius and circularity of the dots of the printed portion formed on the surface of the polyethylene terephthalate film, a laser microscope (e.g., KEYENCE’s VK-9710 laser microscope) is used, and the magnification is set to 10x.

[0217] (Method for determining the radius of the dot in the factor section)

[0218] For the shape of the dot of the printed portion deposited on the surface of each polyethylene terephthalate film, the radius of the circle passing through three points (=radius of the dot of the printed portion) is obtained by analyzing the three points using image analysis software (e.g., VK Analyzer Ver2.4.0.0, analysis software from KEYENCE) with respect to the image observed by the laser microscope above.

[0219] (Evaluation of the circular shape of the dot in the factor section)

[0220] The circularity of the dots in the printed portion formed by the ink applied to the surface of each polyethylene terephthalate film is determined using image analysis software (e.g., WinROOF (Ver 6.6.0) manufactured by Shoji Mitani). Then, the analysis is performed on a shape connecting the center points of the boundary pixels that constitute the outline of the dot. On the analysis screen of WinROOF, this is the value displayed as Circularity II. Then, the circularity of the dots in the printed portion is calculated by the following formula.

[0221] Circularity of the dot in the character section = 4π × (area of ​​the dot) / (periphery of the dot) 2

[0222] The battery packaging material of the present invention may be used for either a primary battery or a secondary battery, but is preferably for a secondary battery. The types of secondary batteries to which the battery packaging material of the present invention is applied are not particularly limited, and examples include lithium-ion batteries, lithium-ion polymer batteries, lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, capacitors, etc. Among these secondary batteries, lithium-ion batteries and lithium-ion polymer batteries may be examples of suitable applications for the battery packaging material of the present invention.

[0223] 5. Polyester film

[0224] The polyester film of the present invention is a polyester film used for use in a polyester film layer located on the outermost surface of a packaging material for batteries. When infrared absorption spectra are acquired in 18 directions in 10° increments from 0° to 170° for the surface of the polyester film using the total internal reflection method of Fourier transform infrared spectroscopy, Y max / Y minIt is characterized by satisfying <1.4. The specific composition (composition, thickness, etc.) of the polyester film of the present invention is identical to the polyester film of the polyester film layer constituting the outermost surface in "2. Each layer forming the packaging material for batteries" above. Furthermore, the measurement of the infrared absorption spectrum on the surface of the polyester film can be performed on the surface facing the outermost surface of the packaging material for batteries in the state of the polyester film alone. In addition, the measurement of the arithmetic mean roughness Ra of the polyester film can also be performed on the surface facing the outermost surface of the packaging material for batteries in the state of the polyester film alone.

[0225] <Example>

[0226] The present invention will be described in detail below by presenting examples and comparative examples. However, the present invention is not limited to the examples.

[0227] Manufacture of packaging materials for batteries

[0228] Packaging materials for each battery of Examples 1 to 3 and Comparative Examples 1 to 7 were prepared by the following method.

[0229] (Example 1)

[0230] Biaxially stretched polyethylene terephthalate film as a substrate layer (thickness 25 μm, surface orientation in Table 1: Y max / Y minA barrier layer consisting of an aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) having an acid-resistant coating formed on both sides was laminated by a dry lamination method on a surface having an arithmetic mean roughness Ra. Specifically, a two-component curing urethane adhesive (a polyol compound and an aromatic isocyanate compound) was applied to one side of the aluminum foil, and an adhesive layer (thickness 3 μm) was formed on the aluminum foil having an acid-resistant coating formed on both sides. Subsequently, the adhesive layer on the aluminum foil and a biaxially stretched polyethylene terephthalate film were laminated, and an aging treatment was performed to produce a laminate of a substrate layer / adhesive layer / barrier layer. In addition, the chemical treatment for forming an acid-resistant film on the aluminum foil used as a barrier layer was performed by applying a treatment solution composed of phenolic resin, a chromium fluoride compound, and phosphoric acid to both sides of the aluminum foil by a roll coating method such that the coating amount of chromium is 10 mg / m² (dry mass), and then baking. In addition, the aluminum foil used as a barrier layer has an acid-resistant film comprising chromium oxide and phosphate.

[0231] Next, maleic anhydride-modified polypropylene (thickness 25 μm) as an adhesive layer and random polypropylene (thickness 55 μm) as a heat-fusible resin layer were co-extruded onto the barrier layer of the obtained laminate, thereby laminating the adhesive layer / heat-fusible resin layer onto the barrier layer. Next, by aging and heating the obtained laminate, a battery packaging material was obtained in which a substrate layer / adhesive layer / barrier layer having acid-resistant coatings on both sides / adhesive layer / heat-fusible resin layer were laminated in this order.

[0232] The analysis of the acid-resistant film was performed as follows. First, the barrier layer and the adhesive layer were separated. At this time, physical peeling was carried out without using water, organic solvents, or aqueous solutions of acids or alkalis. After peeling the barrier layer and the adhesive layer, since the adhesive layer remained on the surface of the barrier layer, the remaining adhesive layer was removed by etching using Ar-GCIB. On the surface of the barrier layer obtained in this manner, the acid-resistant film was analyzed using time-of-flight secondary ion mass spectrometry. As a result, from the acid-resistant film, Ce2PO4 + , CePO4 - Secondary ions composed of Ce, P, and O were detected. Details of the measurement apparatus and measurement conditions for the time-of-flight secondary ion mass spectrometry are as follows.

[0233] Measurement Device: Time-of-Flight (TOF) secondary ion mass spectrometer from ION-TOF. SIMS5

[0234] Measurement conditions

[0235] Primary ion: Double-charged ion of bismuth cluster (Bi3 ++ )

[0236] Primary ion acceleration voltage: 30kV

[0237] Mass range (m / z): 0–1500

[0238] Measurement range: 100㎛×100㎛

[0239] Scan count: 16 scan / cycle

[0240] Number of pixels (1 side): 256 pixels

[0241] Etching ions: Ar gas cluster ion beam (Ar-GCIB)

[0242] Etching ion acceleration voltage: 5.0 kV

[0243] (Example 2)

[0244] Biaxially stretched polyethylene terephthalate film (thickness 25 µm, surface orientation in Table 1: Y max / Y min A packaging material for a battery was obtained in the same manner as in Example 1, except that a lubricant (erucic acid amide (application amount 6 mg / m²) and polyether-modified silicone oil (application amount 1 mg / m²)) was applied to the surface of (having an arithmetic mean roughness Ra) (application amount total 7 mg / m²).

[0245] (Example 3)

[0246] As a substrate layer, a biaxially stretched polyethylene terephthalate film (thickness 12 μm, surface orientation in Table 1: Y max / Y minA laminated film was prepared by dry laminating a biaxially stretched nylon film (thickness 15 μm) and a biaxially stretched polyethylene terephthalate film (having an arithmetic mean roughness Ra) by a dry lamination method. In this laminated film, the biaxially stretched polyethylene terephthalate film and the biaxially stretched nylon film are bonded by a urethane adhesive (thickness after curing 3 μm) using a polyol and an isocyanate curing agent. Next, a barrier layer consisting of an aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) having an acid-resistant coating by performing chemical treatment on both sides was laminated on the biaxially stretched nylon film side by a dry lamination method. Specifically, a two-component polyurethane-based adhesive (a polyol compound and an aromatic isocyanate compound) was applied to one side of the aluminum foil having an acid-resistant coating, and an adhesive layer (thickness 3 μm) was formed on the aluminum foil. Subsequently, by laminating the adhesive layer on the aluminum foil with the biaxially stretched nylon film side of the substrate layer and performing an aging treatment, a laminate was fabricated comprising a substrate layer (biaxially stretched polyethylene terephthalate film / adhesive / biaxially stretched nylon film) / adhesive layer / a barrier layer having acid-resistant films on both sides. Furthermore, the aluminum foil used as the barrier layer has acid-resistant films containing chromium oxide and phosphate on both sides. The analysis of the acid-resistant film on the barrier layer was performed using time-of-flight secondary ion mass spectrometry, as in Example 1. As a result, CrPO2 from the acid-resistant film + , CrPO4 - Secondary ions consisting of Cr, P, and O were detected.

[0247] Next, maleic anhydride-modified polypropylene (thickness 40 μm) as an adhesive layer and random polypropylene (thickness 40 μm) as a heat-fusible resin layer were co-extruded onto the barrier layer of the obtained laminate, thereby laminating the adhesive layer / heat-fusible resin layer onto the barrier layer. Next, the obtained laminate was aged and heated to obtain a battery packaging material in which the substrate layer / adhesive layer / barrier layer / adhesive layer / heat-fusible resin layer are laminated in this order.

[0248] (Comparative Example 1)

[0249] As a biaxially stretched polyethylene terephthalate film of the substrate layer, surface orientation degree as described in Table 1: Y max / Y min A packaging material for a battery was obtained in the same manner as in Example 3, except that a material having an arithmetic mean roughness Ra was used.

[0250] (Comparative Example 2)

[0251] A polyethylene terephthalate film and a nylon film were laminated by co-extrusion, and a biaxially stretched laminated film was prepared. The biaxially stretched polyethylene terephthalate film of the laminated film constituting the substrate layer (thickness 5 μm, surface orientation in Table 1: Y max / Y minBetween the biaxially stretched nylon film (thickness 20 μm) and the arithmetic mean roughness Ra, there is an adhesive layer (thickness 1 μm) composed of polyester (polyester-based elastomer). The laminated film is formed by laminating a biaxially stretched polyethylene terephthalate film / adhesive / biaxially stretched nylon film in sequence. Next, a barrier layer composed of an aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) having an acid-resistant coating applied to both sides by chemical treatment on the surface of the biaxially stretched nylon film side was laminated by a dry lamination method. Specifically, a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil having an acid-resistant coating, and an adhesive layer (thickness 3 μm) was formed. Next, by laminating an adhesive layer on a barrier layer having an acid-resistant film and a biaxially stretched nylon film side of a substrate layer, and then performing an aging treatment, a laminate of a substrate layer (biaxially stretched polyethylene terephthalate film / adhesive / biaxially stretched nylon film) / adhesive layer / barrier layer having an acid-resistant film on both sides was produced.

[0252] Next, an adhesive (thickness after curing of 2 μm) composed of an amorphous polyolefin resin having carboxyl groups and a polyfunctional isocyanate compound was applied and dried at 100°C. Then, the barrier layer side of the obtained laminate and an unoriented polypropylene film (CPP, thickness of 80 μm) were passed between two rolls set at 60°C and bonded, thereby laminating an adhesive layer / thermally fused resin layer onto the barrier layer. Next, by performing an aging treatment, a battery packaging material was obtained in which a substrate layer (biaxially oriented polyethylene terephthalate film / adhesive / biaxially oriented nylon film) / adhesive layer / barrier layer / adhesive layer / unoriented polypropylene film were laminated in this order.

[0253] (Comparative Example 3)

[0254] As a biaxially stretched polyethylene terephthalate film of the substrate layer, surface orientation degree as described in Table 1: Y max / Y min A packaging material for a battery was obtained in the same manner as in Example 3, except that a material having an arithmetic mean roughness Ra was used.

[0255] (Comparative Example 4)

[0256] As a biaxially stretched polyethylene terephthalate film of the substrate layer, surface orientation degree as described in Table 1: Y max / Y min A packaging material for a battery was obtained in the same manner as in Example 3, except that a material having an arithmetic mean roughness Ra was used.

[0257] (Comparative Example 5)

[0258] As a biaxially stretched polyethylene terephthalate film of the substrate layer, surface orientation degree as described in Table 1: Y max / Y min A packaging material for a battery was obtained in the same manner as in Example 3, except that a material having an arithmetic mean roughness Ra was used.

[0259] (Comparative Example 6)

[0260] Biaxially stretched polyethylene terephthalate film (thickness 25 µm, surface orientation in Table 1: Y max / Y min A packaging material for a battery was obtained in the same manner as Comparative Example 2, except that a lubricant (erucic acid amide) was applied (application amount 7 mg / m²) to the surface of (having an arithmetic mean roughness Ra).

[0261] (Comparative Example 7)

[0262] Biaxially stretched polyethylene terephthalate film (thickness 25 µm, surface orientation in Table 1: Y max / Y min A packaging material for a battery was obtained in the same manner as Comparative Example 2, except that a lubricant (erucic acid amide) was applied (application amount 10 mg / m²) to the surface of (having an arithmetic mean roughness Ra).

[0263] Measurement of Surface Orientation

[0264] For the surface of the biaxially stretched polyethylene terephthalate film of each battery packaging material prepared above (the surface opposite to the barrier layer), infrared absorption spectra were acquired in 18 directions from 0° to 170° in 10° increments using the Total Total Reflection (ATR) method of Fourier Transform Infrared Spectroscopy (FT-IR), and for each of the 18 directions, the wavenumber of the corresponding infrared absorption spectrum was 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 (CH2 vertical vibration) and, wavenumber 1410cm -1 Absorption peak intensity Y at 1410 From the value of (C=C stretching vibration) Y 1340 / Y 1410 Calculate each, and the maximum value Y among them max and minimum value Y min From, surface orientation: Y max / Y min ...was calculated. The specific measurement conditions for the infrared absorption spectrum are as follows. The results are shown in Table 1.

[0265] And, for Example 2 and Comparative Examples 6 and 7, the lubricant on the surface of the biaxially stretched polyethylene terephthalate film was wiped off with 2-butanone, and the surface orientation degree was measured on the surface of the biaxially stretched polyethylene terephthalate film.

[0266] (Measurement conditions of infrared absorption spectrum)

[0268] Spectrometer: Thermo Fisher Scientific Nicolet iS10 FT-IR

[0269] Attachment: Single-reflection ATR reflective attachment (Seagull)

[0270] Detector: MCT(Hg Cd Te)

[0271] Wavenumber resolution: 8cm -1

[0272] Accumulated count: 128

[0273] IRE: Ge

[0274] Angle of incidence: 30°

[0275] Polarizer: Wire grid, S polarization

[0276] Baseline: Wavenumber 1800-2000cm -1 Average value of intensity in the range

[0277] Watchtower 1340cm -1 Absorption peak intensity Y at 1340 : Pachycephalus 1335–1342 cm -1 The value obtained by subtracting the baseline value from the maximum peak intensity within the range

[0278] Wisdom 1410cm -1 Absorption peak intensity Y at 1410 : Breakwater 1400–1410 cm -1 The value obtained by subtracting the baseline value from the maximum peak intensity within the range

[0279] The acquisition of infrared absorption spectra in 18 directions was performed by placing a sample with a polyester film exposed horizontally in a sample holder and rotating each Ge crystal placed on the sample by 10°. The angle of incidence is the angle between the perpendicular (normal) and the incident light.

[0280] <Measurement of Arithmetic Mean Roughness Ra of Polyethylene Terephthalate Film Surface>

[0281] In accordance with the method specified in JIS B 0601-2001, the arithmetic mean roughness Ra was measured on the surface of the biaxially stretched polyethylene terephthalate film (polyester film layer) constituting the outermost surface of each battery packaging material obtained above. As the measuring device for the arithmetic mean roughness Ra, a Zygo NewView 7300 white interferometer was used, and measurements were performed under the conditions of a measurement area of ​​0.22 mm (objective lens 50x, zoom lens 1x) and tilt correction (Cylinder). The arithmetic mean roughness Ra was measured in the state of the battery packaging material. Furthermore, no operations such as wiping the surface of the polyethylene terephthalate film were performed during the measurement. The results are shown in Table 1.

[0282] <Evaluation of the surface properties of polyethylene terephthalate films>

[0283] In an environment with a temperature of 24°C and a relative humidity of 50%, ink was applied to the surface of the biaxially stretched polyethylene terephthalate film of each battery packaging material prepared above using an inkjet printer (Markem Image 9040 (1.1M head) manufactured by Markem Image Co., Ltd.) and dried for 10 seconds. Next, the printability of the biaxially stretched polyethylene terephthalate film surface was evaluated based on the radius and circularity of the dots of the printed area formed on the surface of the biaxially stretched polyethylene terephthalate film. The printing setting conditions were set as follows: ink viscosity: 3.4 cps, temperature: 34°C, pressure: 270 bar, nozzle size: diameter 50 μm, resolution (dot density): 115 dpi. The measurement method for the radius and circularity of the dots of the printed area is as described below. The evaluation was conducted in the state of the battery packaging material. In addition, the radius and circularity of the dots of the printed area were taken as average values ​​with a number of 3. Also, when performing the evaluation, operations such as wiping the surface of the polyethylene terephthalate film were not performed. The results are shown in Table 1.

[0284] The distance between the inkjet printer print head and the surface of the biaxially stretched polyethylene terephthalate film was set to 20 mm, and 5157E standard ink was used.

[0285] In addition, a laser microscope (KEYENCE VK-9710 laser microscope) was used to observe the radius and circularity of the dots of the printed portion formed on the surface of the biaxially stretched polyethylene terephthalate film, and the magnification was set to 10x. For reference, images of the printed portion formed on the surface of the biaxially stretched polyethylene terephthalate film, observed with a laser microscope for Example 2 and Comparative Example 7, are shown in FIG. 4 (Example 2) and FIG. 5 (Comparative Example 7), respectively.

[0286] (Method for measuring the radius of the dot in the factor section)

[0287] The shape of the dots of the printed portion deposited on the surface of each biaxially stretched polyethylene terephthalate film was analyzed using the analysis software VK Analyzer Ver2.4.0.0 from KEYENCE on the image observed with the laser microscope above, and the radius of the circle passing through three points (=radius of the dots of the printed portion) was calculated by three-point circle analysis. The results are shown in Table 1.

[0288] (Evaluation of the circular shape of the dot in the factor section)

[0289] The circularity of the dots in the printed portion formed by ink applied to the surface of each biaxially stretched polyethylene terephthalate film was measured using the image analysis software WinROOF (Ver 6.6.0) manufactured by Shoji Mitani. The analysis was performed on a shape connecting the center points of the boundary pixels constituting the outline of the dots. In the analysis screen of WinROOF, this value is displayed as Circularity II. The circularity of the dots in the printed portion is calculated by the following formula. The circularity of the dots in the printed portion was evaluated according to the following criteria. The results are shown in Table 1. For reference, the measured values ​​of the circularity of the dots in the printed portion for Example 2 (Fig. 4) and Comparative Example 7 (Fig. 5) are shown in Table 1.

[0290] Circularity of the dot in the character section = 4π × (area of ​​the dot) / (periphery of the dot) 2

[0291] A: The circularity of the dots in the printed portion is 0.725 or higher, and on the surface of a biaxially stretched polyethylene terephthalate film, the dots in the printed portion have a clean circular shape.

[0292] B: The circularity of the dots in the printed portion is 0.700 or higher and less than 0.725, and on the surface of a biaxially stretched polyethylene terephthalate film, the dots in the printed portion have a distorted circular shape.

[0294] [Table 1]

[0295]

[0296] The battery packaging materials of Examples 1 to 3 have a polyester film layer constituting the outermost surface, formula: Y max / Y minIt satisfies the relationship <1.4, the radius of the dots in the printed portion is small, and the evaluation of the circularity of the dots in the printed portion is also excellent, resulting in excellent printing suitability. From the results of Examples 1 to 3, it can be seen that excellent printing suitability is exhibited regardless of whether a lubricant is present on the surface of the polyester layer. In contrast, the battery packaging materials of Comparative Examples 1 to 7 have a polyester film layer constituting the outermost surface, with formula: Y max / Y min The relationship <1.4 was not satisfied, the radius of the dot in the printing area was large, or the evaluation of the circularity of the dot in the printing area was poor. For example, in Comparative Example 7, the radius of the dot in the printing area was small, but the circularity was small at 0.723, and the dot in the printing area on the surface of the polyethylene terephthalate film layer had a distorted circular shape, and the printing suitability was poor (see Fig. 5). In Comparative Example 6, a lubricant was present on the surface of the polyester layer, and the radius of the dot in the printing area was about the same as in Comparative Example 2, but the radius of the dot in the printing area was larger than in Examples 1 to 3, and the printing suitability was poor. Furthermore, in Comparative Example 7, in which the amount of lubricant was increased compared to Comparative Example 6, as described above, the radius of the dot in the printing area was small, but the dot in the printing area had a distorted circular shape, and the printing suitability was poor. Explanation of the symbols

[0297] 1 : Base layer 2: Adhesive layer 3 : Barrier layer 4: Heat-fusible resin layer 5: Adhesive layer

Claims

Claim 1 A battery packaging material: Y, comprising a laminate having, at least, a substrate layer located at the outermost surface, a barrier layer, and a heat-fusible resin layer in this order, wherein the outermost surface of the substrate layer is composed of a polyester film layer, the polyester film layer is a multilayer, and when infrared absorption spectra are acquired in 18 directions at 10° increments from 0° to 170° on the surface of the polyester film layer using the total internal reflection method of Fourier transform infrared spectroscopy, the following equation is satisfied. max / Y min <1.4 Among the above formulas, Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by, and Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by. Claim 2 A battery packaging material: Y, comprising a laminate having, at least, a substrate layer located at the outermost surface, a barrier layer, and a heat-fusible resin layer in this order, wherein the outermost surface of the substrate layer is composed of a polyester film layer, the substrate layer is composed of a single layer of the polyester film layer, and when infrared absorption spectra are acquired in 18 directions at 10° increments from 0° to 170° with respect to the surface of the polyester film layer using the total internal reflection method of Fourier transform infrared spectroscopy, the following equation is satisfied. max / Y min <1.4 Among the above formulas, Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by, and Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by. Claim 3 A battery packaging material used for the purpose of performing printing on the surface of the polyester film layer in accordance with claim 1 or 2. Claim 4 A battery packaging material according to claim 1 or 2, in accordance with the method specified in JIS B 0601-2001, wherein the arithmetic mean roughness Ra measured on the surface of the polyester film layer is 10 nm or more. Claim 5 A battery packaging material according to claim 1 or 2, wherein an adhesive layer is provided between the barrier layer and the heat-fusible resin layer, and the adhesive layer comprises an acid-modified polyolefin. Claim 6 A battery packaging material according to claim 5, wherein the thickness of the adhesive layer is 50㎛ or less. Claim 7 A battery packaging material according to claim 5, wherein the thickness of the adhesive layer is 20㎛ or less. Claim 8 A packaging material for a battery according to claim 1 or 2, wherein the thickness of the barrier layer is 85㎛ or less, the thickness of the barrier layer is 50㎛ or less, or the thickness of the barrier layer is greater than 50㎛ and less than or equal to 85㎛. Claim 9 A battery packaging material according to claim 1, wherein the thickness of the substrate layer is greater than 40㎛ and less than or equal to 50㎛. Claim 10 A packaging material for batteries according to claim 1 or 2, wherein the thickness of the polyester film layer is 10㎛ or more and 25㎛ or less. Claim 11 A method for manufacturing a battery packaging material: Y, comprising a process of obtaining a laminate by laminating a substrate layer, a barrier layer, and a heat-fusible resin layer located at the outermost surface in this order, wherein the outermost surface of the substrate layer is composed of a polyester film layer, the polyester film layer is a multilayer, and when infrared absorption spectra are acquired in 18 directions in 10° increments from 0° to 170° on the surface of the polyester film layer using the total internal reflection method of Fourier transform infrared spectroscopy, the method satisfies the following equation: max / Y min <1.4 Among the above formulas, Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by, and Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by. Claim 12 A method for manufacturing a battery packaging material: Y, wherein the laminate comprises, at least, a substrate layer located at the outermost surface, a barrier layer, and a heat-fusible resin layer in this order, the outermost surface of the substrate layer is composed of a polyester film layer, the substrate layer is composed of a single layer of the polyester film layer, and when infrared absorption spectra are acquired in 18 directions at 10° increments from 0° to 170° on the surface of the polyester film layer using the total internal reflection method of Fourier transform infrared spectroscopy, the following equation is satisfied: max / Y min <1.4 Among the above formulas, Y max is, in each of the above 18 directions, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹ -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the maximum value among the values ​​divided by, and Y min For each of the 18 directions mentioned above, the wavenumber of the infrared absorption spectrum is 1340 cm⁻¹. -1 Absorption peak intensity Y at 1340 Eul, Pasu 1410cm -1 Absorption peak intensity Y at 1410 It is the minimum value among the values ​​divided by. Claim 13 A method for manufacturing a packaging material for a battery according to claim 11 or 12, comprising a process of obtaining a laminate by laminating the substrate layer, the barrier layer, the adhesive layer, and the heat-fusible resin layer located at the outermost surface in this order, wherein the adhesive layer and the heat-fusible resin layer are laminated by a co-extrusion lamination method or a thermal lamination method. Claim 14 A method for manufacturing a battery packaging material according to claim 11 or 12, comprising a process of obtaining a laminate by laminating the substrate layer, the barrier layer, the adhesive layer, and the heat-fusible resin layer located at the outermost surface in this order, wherein the adhesive layer and the heat-fusible resin layer are laminated by a sandwich lamination method.

Citation Information

Patent Citations

  • Polyester film for vapor deposition

    JP1997104769A

  • Packaging material for battery

    KR1020170046725A

  • Polarizing plate

    KR1020180107221A

  • Multi-layer laminated film

    WO2016204146A1

  • Packaging material for batteries, method for producing same and battery

    WO2017179636A1